Menstrual hygiene practices of women in a rural area of Kancheepuram district, India: a cross sectional study - Grace G., Angeline; M., ArunKumar; R., Umadevi (International Journal Of Community Medicine And Public Health, 2019)
Background: Menstruation is a normal biological function in females and in the society, the practices followed are highly variable across different regions. This study aimed to determine the practices followed during menstruation by rural women in Kancheepuram district, Tamil Nadu, India. Methods: This community based cross sectional study was carried out between August and October 2018. Sample size of 400 was calculated by using formula 4pq/d2 and female respondents were selected from sampled households using systematic random sampling. Data were collected using a pre-tested, structured questionnaire, which were analysed using SPSS version 16.0 and presented using descriptive and analytical statistics. Results: A total of 395 women were included in the study. About 54% of females belonged to the age group of 26-35 years and 82.5% were married. Use of sanitary pads during menstruation was reported by 28.6% of the females. Other absorbents used were disposable cloths (46.3%) and reusable cloths (25.1%). About 79% of females practiced some form of restriction during menstruation. Females aged <35 years (OR: 2.55, 95% CI: 1.48-4.39) were more likely to use sanitary pad compared to older females. Females who used sanitary pad as absorbent were less likely to have symptoms of reproductive tract infections compared to those who didn’t (OR: 0.51, 95% CI: 0.28-0.94). Conclusions: Menstrual hygiene practices were found be unsatisfactory among the rural women and various restrictions during menstruation were also in practice. Women should be educated about the importance of use of sanitary pads and the harms of using cloths. Awareness also needs to be created to abolish the unnecessary restrictions that are imposed on women to be followed during menstruation.